MEDIUM-TERM RESULTS OF TOTAL ELBOW ARTHROPLASTY IN PATIENTS WITH RHEUMATOID ARTHRITIS - A. G. Aliev; R. M. Tikhilov; I. I. Shubnyakov; A. N. Kovalenko; A. V. Ambrosenkov; A. P. Antipov (Научно-практическая ревматология)
The success of total elbow arthroplasty (TEA) over the past decades could improve the functional results of this surgery. However, the frequency of complications and reinterventions remains high. In the Russian literature, there is a small number of publications that describe investigations of the results of TEA in patients with rheumatoid arthritis (RA).Objective: to assess the medium-term results of primary total replacement of the elbow joint (EJ) in patients with its rheumatoid injury and to identify potential risk factors for endoprosthetic loosening.Subjects and methods. A group of 78 patients who had undergone replacement of EJ (a total of 81 joints) in 2000 to 2017 was retrospectively studied. The mean postoperative follow-up period was 3.3 (1.1 to 4.9) years. The data of clinical examination, radiography, and functional scales were taken into account. The survival rate of various endoprostheses was calculated using the Kaplan-Meier method. The potential risk factors for implant loosening were investigated.Results and discussion. Aseptic loosening was recorded in 8.4% of cases; there was deep infection (2.4%) and dissociation (2.4%) of EJ components. The five-year survival rates for all EJs were 75.0%. The significant risk factors for loosening were surgical technique errors; use of an Arete endoprosthesis; a preoperative C-reactive protein level of higher than 36.1 mg/l; age of older than 59 years at surgery; and a body mass index of higher than 32 kg/m2.Conclusion. Despite advances in TEA, the medium-term incidence of complications is quite high. Preservation of the integrity of bone tissue and capsule-ligament apparatus at the moment of surgery, correct surgical technique, and use of high-quality prostheses will be able to provide long-term EJ endoprosthesis survival.